Emulsifier-Free Acrylate-Based Emulsion Prepared by Reverse Iodine Transfer Polymerization - Huang, Tao (Polymers (Basel), 2020)
The self-emulsifying acrylate-based emulsions with solid content 45 wt.% were prepared in 3.5 h by reverse iodine transfer polymerization (RITP), and the polymer molecular weight (M(n)) could be 30,000 g·mol(−1). The influences of methacrylic acid (MAA) amount, soft/hard monomer mass ratio, and iodine amount on polymerization and latex were investigated. A moderate amount of ionized MAA was needed to stabilize the emulsion. Glass transition temperature (T(g)) was decreased with the increasing mass ratio of soft/hard monomer. A higher iodine amount resulted in lower M(n). The increased M(n) after chain extension of the polymer with water-insoluble monomers in iterative one-pot method proved the living of polymer. Compared with conventional emulsion polymerization, molecular weight (M(n)) could be controlled, and M(n) of polymer synthesized in RITP emulsion polymerization is higher; emulsion of polyacrylate-containing hydroxyl monomer units prepared by RITP emulsifier-free radical polymerization is more stable. Good properties, such as hardness, water resistance, adhesion, and increased value of maximum tensile of films modified by reaction of polyacrylate with melamine–formaldehyde (MF) resin, indicated potential application in baking coating.